COMMUNICATION ASPECTS BETWEEN THE NURSE AND THE IMMOBILE PATIENT - Popovičová, M. (Україна. Здоров’я нації, 2023)
Usually, when sick people are admitted to a hospital, they expect from medical staff kind behavior. They are handicapped by their illness and altered health status. That is why it is in the hands of the staff to overcome the barriers towards the sick person. It should be about an enriching exchange of views, communication. It is important to use empathy, trueness – that is, openness, specificity, concreteness. It is also necessary to prove to the patient his interest in him as a human being. Show heart, kindness and never unconcern. Respect him as a unique, unrepeatable being.